EVALUATION OF THE USE OF FILTER MEDIA FROM CHICKEN EGG SHELL AND GREEN MUSSELS SHELL WASTE ON NILE TILAPIA (Oreochromis niloticus) CULTIVATION IN THE RAS (RECIRCULATING AQUACULTURE SYSTEM) - Alif Kurniawan; Farikhah (Universitas Mataram, 2026)
Tilapia (Oreochromis niloticus) culture faces water quality challenges due to the accumulation of metabolic waste and uneaten feed. Recirculating aquaculture systems (RAS) can improve water quality, but commercial filter media are relatively expensive for small-scale farmers. Waste materials such as mussel shells, eggshells, and zeolite have potential as economical alternatives. Therefore, research is needed to evaluate the effectiveness of waste-based filter media in maintaining water quality and fish growth. This study aimed to analyze the effect of waste filter media in RAS on water quality and tilapia growth and to determine an economical alternative for small-scale farmers. A descriptive study was conducted for 28 days in Bungah Village, Gresik, using three filter media treatments. The treatments consisted of P1 (foam + mussel shell + bioball), P2 (foam + eggshell + bioball), and P3 (foam + zeolite + bioball) with a stocking density of 14 fish per aquarium. Observed parameters included pH, growth (WG, SGR), and FCR. Results showed that all treatments-maintained pH within the optimal range with minimal fluctuation. Treatments P1 and P3 produced higher growth compared to the others. FCR values in all treatments indicated good and relatively similar feed efficiency. Mussel shell and zeolite media provided more consistent biological performance. Eggshell media also maintained water quality although growth was slightly lower. Overall, waste-based filter media performed comparably to commercial filters. Waste filter media in RAS effectively maintained water quality and supported tilapia growth. Utilization of waste materials has potential as an economical alternative for small-scale farmers.